The Analysis of Spiritual and Social Attitudes in the Science-Biology Learning Process of students Class VIII of SMPN 20 Padang - Puspitasari, Winda; Anhar, Azwir; Zulyusri, Zulyusri; Ristiono, Ristiono (BIO-EDU: Jurnal Pendidikan Biologi, 2020)
The attitude assessment of the 2013 curriculum is needed to prepare a moral and civilized generation by following the objectives of this curriculum. This study aims to determine the spiritual and social attitudes in the Science-Biology learning process of students Class VIII SMPN 20 Padang. aspects observed are 1)respecting and soulful the teachings of the religion they hold, 2)honest, 3)discipline 4)responsibility, 5)polite, 6)self-confidence, 7)caring. This type of research is descriptive research. Data collection using questionnaires and observation sheets then conducted a percentage analysis to determine the average score obtained from the two assessment techniques. The Data obtained will be shown through images. The result of this research is the assesement of spiritual and social attitudes during the learning process of Sciences-Biology learning process of students Class VIII of SMPN 20 Padang have a good criteria. Spiritual attitude of students Class VIII of SMPN 20 Padang have a good criteria in the aspect of respecting and soulful the teachings of the religion they hold. Social attitudes of students Class VIII of SMPN 20 Padang have a good criteria on the five aspects of attitudes observed, such as 1) discipline, 2) responsibility, 3) polite, 4) self-confidence, and 5) caring, while one other aspect of attitude have a enough criteria, namely aspects of honest attitude.